Effect of clinical signs, endocrinopathies, timing of surgery, hyperlipidemia, and hyperbilirubinemia on outcome in dogs with gallbladder mucocele. (September 2019) - Jaffey, J.A.; Pavlick, M.; Webster, C.R.; Moore, G.E.; McDaniel, K.A.; Blois, S.L.; Brand, E.M.; Reich, C.F.; Motschenbacher, L.; Hostnik, E.T.; Su, D.; Lidbury, J.A.; et al.
Abstract: Gallbladder mucocele (GBM) is a common extra-hepatic biliary syndrome in dogs with death rates ranging from 7 to 45%. Therefore, the aim of this study was to identify the association of survival with variables that could be utilized to improve clinical decisions. A total of 1194 dogs with a gross and histopathological diagnosis of GBM were included from 41 veterinary referral hospitals in this retrospective study. Dogs with GBM that demonstrated abnormal clinical signs had significantly greater odds of death than subclinical dogs in a univariable analysis (OR, 4.2; 95% CI, 2.14–8.23; P  < 0.001). The multivariable model indicated that categorical variables including owner recognition of jaundice (OR, 2.12; 95% CI, 1.19–3.77; P  = 0.011), concurrent hyperadrenocorticism (OR 1.94; 95% CI, 1.08–3.47; P  = 0.026), and Pomeranian breed (OR, 2.46; 95% CI 1.10–5.50; P  = 0.029) were associated with increased odds of death, and vomiting was associated with decreased odds of death (OR, 0.48; 95% CI, 0.30–0.72; P  = 0.001). Continuous variables in the multivariable model, total serum/plasma bilirubin concentration (OR, 1.03; 95% CI, 1.01–1.04; P  < 0.001) and age (OR, 1.17; 95% CI, 1.08–1.26; P  < 0.001), were associated with increased odds of death. The clinical utility of total serum/plasma bilirubin concentration as a biomarker to predict death was poor with a sensitivity of 0.61 (95% CI, 0.54–0.69) and a specificity of 0.63 (95% CI, 0.59–0.66). This study identified several prognostic variables in dogs with GBM including total serum/plasma bilirubin concentration, age, clinical signs, concurrent hyperadrenocorticism, and the Pomeranian breed. The presence of hypothyroidism or diabetes mellitus did not impact outcome in this study.